Fengycin–essential oil emulsions as sustainable biocontrol formulations against Moniliophthora roreri, the cacao frosty pod rot pathogen - Villavicencio-Vásquez, Mirian; Espinoza-Lozano, Fernando; Chóez-Guaranda, Ivan; Cos-Farias, Valeria; Coronel-León, Jonathan (Frontiers in Plant Science, 2026)
IntroductionMoniliophthora roreri, the causal agent of cacao frosty pod rot (FPR), represents a major constraint to cacao production in tropical regions. The increasing demand for eco-compatible crop protection strategies highlights the need for synergistic bioformulations combining microbial and plant-derived antifungal agents.MethodsIn this study, we evaluated the antifungal activity and physicochemical stability of emulsions formulated with fengycin, a cyclic lipopeptide produced by Bacillus subtilis DS03, and essential oils (EOs) from cinnamon (Cinnamomum zeylanicum) and peppermint (Mentha piperita). Fengycin isoforms were identified by mass spectrometry (m/z 1435–1491). Antifungal activity against M. roreri was assessed individually and in combination using inhibition assays, fractional inhibitory concentration (FIC) indices, and colloidal stability measurements (ζ-potential).ResultsFengycin inhibited mycelial growth of M. roreri by 84.6% at 1000 ppm, while cinnamon EO achieved complete inhibition at concentrations ≥500 ppm. Fengycin–cinnamon (F–C) emulsions showed strong synergistic antifungal activity (FIC < 0.5) and high colloidal stability (ζ = –26 to –35 mV). In contrast, fengycin–peppermint (F–P) emulsions exhibited additive effects (FIC ≈ 1).DiscussionThe enhanced antifungal efficacy of F–C emulsions is attributed to the dual role of fengycin as both an antifungal compound and a natural biosurfactant, which improves the dispersion and bioavailability of cinnamaldehyde-rich essential oils. These findings demonstrate the potential of a stable, bio-based antifungal formulation that integrates microbial and plant metabolites, offering a scalable and sustainable strategy for controlling fungal diseases in cacao and other crops.